IMPLEMENTASI PERMAINAN ENGKLEK DALAM MENINGKATKAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI RA AL-KHAIRIYAH - Nadifah, Robiatun; Hidayat, Amat; Rini, Ratu Yustika (LPPM Universitas Bina Bangsa, 2025)
Engklek game is a traditional game that involves physical activity in the form of jumping on one leg, walking, and maintaining balance. This study aims to examine the implementation of the engklek game in improving the gross motor skills of children aged 4-5 years at RA Al-Khairiyah. This activity is believed to be able to stimulate the development of gross motor skills in early childhood. Gross motor skills include large body movements such as walking, jumping, and running which require muscle coordination and physical strength. This study uses a qualitative research method with a descriptive approach. The objects of this study were 15 children. The results of the study showed that the implementation of the engklek game can improve gross motor skills, there is an increase in balance, muscle strength, and motor coordination after playing regularly. The success factors of the engklek game are influenced by the active involvement of children, teacher support, and consistent frequency and duration of the game. From the results of this study, it can be concluded that the engklek game is one of the effective learning methods in developing the gross motor skills of early childhood. This game can be used as a routine activity at school, because besides being easy to do, it also does not require complicated equipment.